Metastatic chromophobe renal cell carcinoma treated with targeted therapies: A Renal Cross Channel Group study. (July 2017) - Colomba, Emeline; Le Teuff, Gwénaël; Eisen, Tim; Stewart, Grant D.; Fife, Kate; Larkin, James; Biondo, Andrea; Pickering, Lisa; Srinivasan, Anandagopal; Boyle, Helen; Derosa, Lisa; Sternberg, Cora N.; et al.
Abstract: Background: Treatment of non–clear cell renal cell carcinoma (RCC) remains controversial despite several recent prospective studies of targeted therapies (TT). Often Vascular Endothelial growth Factor (VEGF) and Mammalian Target of Rapamycin (mTOR) inhibitors are used, extrapolating the data from use of these agents in clear cell RCC. Methods: We performed a retrospective data analysis within the Renal Cross Channel Group to determine metastatic chromophobe RCC (mChRCC) outcomes in the TT era. The end-points were overall response, overall survival (OS) and time to treatment failure (TTF). The two latter were estimated using the Kaplan–Meier method. Results: 91 mChRCC patients from 26 centres were included. Median follow-up from the date of first metastasis was 6.1 years (range: 0–13.9). Median OS was 37.9 months (95% confidence interval [CI]: 21.4–46.8) from the diagnosis of metastatic disease. Among the 61 patients who received TT, 50 (82%) were treated with anti-angiogenic (AA) and 11 with mTOR inhibitors. Median TTF and OS in patients receiving a first line of AA was 8.7 months (95% CI: 5.2–10.9) and 22.9 months (95% CI: 17.8–49.2) versus 1.9 months (95% CI: 1.0–6.0) and 3.2 months (95% CI: 2.3–not evaluable) with mTOR inhibitors, respectively. A stratified log-rank test was used to compare AA and mTOR inhibitors TT, while controlling the effect of the International Metastatic RCC Database Consortium risk group and no significant difference between AA and mTOR inhibitors was observed for TTF (p = 0.26) or for OS (p = 0.55). Conclusion: We report the largest retrospective cohort of patients with mChRCC treated with TT and no significant difference between AA and mTOR inhibitors was observed for TTF and OS. Highlights: We describe the largest cohort, to date, of metastatic chromophobe renal cell carcinoma (mChRCC) treated with targeted therapy. Anti-angiogenic is an option for the treatment of patients with mChRCC. Median overall survival for mChRCC treated with anti-angiogenic is 22.9 months.